Environmental impact assessment for a polder container terminal in Singapore - Chua, Edmund Weiqiang (2016)
Singapore relies heavily on land reclamation to meet increasing needs for new land space. The increasing rate of land reclamation have resulted in the devastation of environmental valued receptors such as corals and mangroves. To study the impact of land reclamation on the ecology, we have to implement Environmental Impact Assessment (EIA) towards the land reclamation process to understand how it affects the environment. In this report we will explore the use of a new land reclamation technique that involves the construction of a polder. In particular, we will focus on the increase in sediment content arising from the construction process of a polder container terminal and assess how it will affect the surroundings. A seven step EIA framework have been created due to the lack of a recommended framework in Singapore. Tuas have been chosen to be the study area for the EIA framework as it is currently the prime location for land reclamation of a polder container terminal and the data for its climate is more readily available for this study. After applying the EIA framework onto the Tuas climate, it is found that the increase in sediment content would likely not cause any significant impacts to the valued receptors in the area. The far proximity of the receptors from the reclamation area is crucial in minimising the impact of the use of the polder design. Comparing the impact assessed for the polder design to the expected results of a conventional land reclamation, we can conclude that the polder is likely to have a lesser environmental impact and hence is more suitable for land reclamation in Tuas.